2008
DOI: 10.1007/s12204-008-0275-5
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and analysis of flexible solar panels’ deployment and locking processes

Abstract: To predict the attitude of satellite during the whole deployment process and evaluate the locking impact, a numerical flexible model of a certain satellite associated with four flexible honeycomb solar panels was established. The flexible solar panel was modeled by the finite element analysis (FEA), and the motion equations were derived by Lagrangian formulation. The locking process was based on the method of Hertzian contact, which enables one to predict the locking impact on the satellite and the subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Many references in the literature study the dynamics of spacecrafts with flexible appendages, like solar panels or antennas. [23][24][25][26][27][28] There are three main computational difficulties associated with very flexible space structures, 29 namely the stiff character of the equations of motion, the coupling between axial and bending effects and the problems associated with large deformations. Stiffness is tackled using implicit integration schemes, that usually improve stability introducing numerical damping in the high-frequency range.…”
Section: Satellite's Manoeuvrementioning
confidence: 99%
See 1 more Smart Citation
“…Many references in the literature study the dynamics of spacecrafts with flexible appendages, like solar panels or antennas. [23][24][25][26][27][28] There are three main computational difficulties associated with very flexible space structures, 29 namely the stiff character of the equations of motion, the coupling between axial and bending effects and the problems associated with large deformations. Stiffness is tackled using implicit integration schemes, that usually improve stability introducing numerical damping in the high-frequency range.…”
Section: Satellite's Manoeuvrementioning
confidence: 99%
“…Each panel is hinged to the satellite body by three smooth spherical joints (see Figure 9) and connected by four rigid and massless bars, acting as stiffeners of the panels. The satellite body is equipped with two rockets R 1 and R 2 that provide the necessary thrust, given by (27) expressed in kN, to perform the manoeuvre aimed at changing the attitude of the satellite by 90 . The motion is illustrated in Figure 10.…”
Section: Satellite's Manoeuvrementioning
confidence: 99%
“…Joint friction could affect the deploying process of solar arrays. Up to now, the flexibility of solar arrays is another issue that does not receive in-depth study (Gao et al , 2008). Along with the development of space technology, solar arrays become larger, so the flexibility should be paid more attention to in the dynamics analysis of solar array deployment.…”
Section: Introductionmentioning
confidence: 99%
“…XS Ge and YZ Liu 5 derived the Euler's equations of forced vibration of two flexible solar arrays and discussed attitude stability of flexible spacecraft. E Gao et al 6 presented the methodology on modeling and simulating the deployment and locking processes of flexible solar panels for a satellite and revealed that the deployment process of flexible solar panels impacted the attitude of satellite. These researches provide a significant foundation for studying the dynamic characteristics of deployable flexible solar array system during deployment.…”
Section: Introductionmentioning
confidence: 99%